Saloons of the old West. - Erdoes, Richard (Alfred A. Knkopf New York, 1979)
History of the rowdy, rambunctious, violent and colorful western saloons. Crammed with anecdote, fact and legend.
Includes Index and Bibliography
Keywords: Saloons -- History -- the West; Old West -- History -- American